2011
DOI: 10.1111/j.1755-3768.2011.02130.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity, ocular blood flow and their potential role in assessing ischaemic retinal disease

Abstract: ABSTRACT.Purpose: To examine the definition, evaluation methodology, association to ocular blood flow and potential clinical value of contrast sensitivity (CS) testing in clinical and research settings, focusing in patients with ischemic retinal disease. Methods: A review of the medical literature focusing on CS and ocular blood flow in ischemic retinal disease. Results: CS may be more sensitive than other methods at detecting subtle defects or improvements in primarily central retinal ganglion cell function e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 114 publications
(183 reference statements)
0
19
0
Order By: Relevance
“…Several groups have documented reduced velocity of ocular blood flow in both early and late stage retinitis pigmentosa compared to normal controls; [28][29][30][31][32] however, no previous longitudinal or experimental studies have adequately explored the relationship between changes in ocular blood flow velocity and either improvements or reductions in visual function in retinitis pigmentosa. The relationship between vascular and visual function in retinal ischaemia has been described previously 33 and it might also play a role in patients with retinitis pigmentosa after acupuncture.…”
Section: Discussionmentioning
confidence: 64%
“…Several groups have documented reduced velocity of ocular blood flow in both early and late stage retinitis pigmentosa compared to normal controls; [28][29][30][31][32] however, no previous longitudinal or experimental studies have adequately explored the relationship between changes in ocular blood flow velocity and either improvements or reductions in visual function in retinitis pigmentosa. The relationship between vascular and visual function in retinal ischaemia has been described previously 33 and it might also play a role in patients with retinitis pigmentosa after acupuncture.…”
Section: Discussionmentioning
confidence: 64%
“…4 Twenty-eight eyelids of 14 patients showed statistically significant mean increases in contrast sensitivity after upper eyelid blepharoplasty, resulting in brighter vision. Dermatochalasis was found to be responsible for the field defects because the results were reversed after redundant skin was taped up or following blepharoplasty.…”
Section: Discussionmentioning
confidence: 96%
“…The mean intraocular pressure (IOP) in controls was 15.02 ± 3.201 (10-24) mm Hg, in disc suspects 13.84 ± 3.133 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) mm Hg and in glaucoma patients 13.11 ± 3.099 (6-22) mm Hg. The distribution of IOP was not similar across the study groups, χ 2 = 7.020, P = 0.03.…”
Section: Intraocular Pressurementioning
confidence: 99%
“…Richman et al [7] found that contrast sensitivity loss correlated more closely and strongly to glaucomatous damage than binocular visual field loss in patients with glaucoma. Contrast sensitivity testing thus may be more sensitive to subtle changes in visual function when compared to other commonly used tests such as visual field and visual acuity evaluating retinal function and thus may also be able to detect glaucomatous changes even prior to visual field and structural changes [8]. This belief led to the development of Spaeth Richman Contrast Sensitivity Test (SPARCS) for detecting contrast sensitivity for patients with glaucoma.…”
Section: Introductionmentioning
confidence: 99%